Sobre las causas de la sustitución de cantare habeo por cantaré - Sobczak, Witold (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The aim of the article is to comment on the reasons for the replacement of the analytic future form (cantare habeo) by the synthetic one (cantaré) in Medieval Spanish. Undoubtedly, we are dealing with a process considered to be a linguistic change, which was triggered not only by a series of different morphological and phonological factors, but also by those of a semantic and syntactic nature. We should nonetheless bear in mind that this replacement basically meant a change in the formal expression of posteriority. For this reason, its creation did not prove to be so innovative, unlike, for example, the appearance of cantaría, which was a completely new and nonexistent conjugation verbal category in Latin.